2013
DOI: 10.1136/jmedgenet-2013-101951
|View full text |Cite
|
Sign up to set email alerts
|

Autism traits in the RASopathies

Abstract: Background Mutations in Ras/mitogen-activated protein kinase (Ras/MAPK) pathway genes lead to a class of disorders known as RASopathies, including neurofibromatosis type 1 (NF1), Noonan syndrome (NS), Costello syndrome (CS), and cardio-facio-cutaneous syndrome (CFC). Previous work has suggested potential genetic and phenotypic overlap between dysregulation of Ras/MAPK signalling and autism spectrum disorders (ASD). Although the literature offers conflicting evidence for association of NF1 and autism, there has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(185 citation statements)
references
References 72 publications
10
165
3
Order By: Relevance
“…22 Of note, germline variants in PTEN present the ASD, obesity, and macrocephaly triad of phenotypes, [66][67][68][69][70] whereas those in the Ras/MAPK signaling pathway are associated with social impairment. 71 The interactions observed at this cluster of genes, both at the chromatin and genetic level, suggest that the CNVprone non-overlapping loci at 16p11.2 should be approached and studied as ''connected regions'' rather than completely independent entities.…”
Section: Discussionmentioning
confidence: 99%
“…22 Of note, germline variants in PTEN present the ASD, obesity, and macrocephaly triad of phenotypes, [66][67][68][69][70] whereas those in the Ras/MAPK signaling pathway are associated with social impairment. 71 The interactions observed at this cluster of genes, both at the chromatin and genetic level, suggest that the CNVprone non-overlapping loci at 16p11.2 should be approached and studied as ''connected regions'' rather than completely independent entities.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluated clinically using DSM-IV-TR (American Psychiatric Association 2000) criteria, none of these children were found to meet diagnostic criteria for ASD. In another study by Adviento et al (2014), 21 % of participants with NS showed elevated ASD symptoms on the SCQ screening measure, which was significantly different than the rate of elevated scores found in a sibling comparison group (0 %). Scores on the Social Responsiveness Scale (SRS; Constantino and Gruber 2005), another screening measure of ASD symptoms, were also significantly higher in the NS group than the sibling group.…”
Section: Autism Spectrum Disordermentioning
confidence: 95%
“…A number of studies have shown that mutations in genes acting more downstream in the RAS-MAPK pathway (e.g., BRAF, MEK 1, MEK2, HRAS), which typically cause CFC syndrome and Costello syndrome, tend to be associated with greater impairments in neurological, intellectual, and adaptive functioning than mutations in genes encoding components or regulators that act more upstream in the pathway (e.g., NF1, PTPN11, SOS1, RAF1), which cause NF1 and NS (Cesarini et al 2009;Pierpont et al 2010b;Yoon et al 2007). Individuals with gene mutations acting downstream in the pathway (especially those diagnosed with CFC syndrome) also tend to have a higher prevalence of autisticlike traits (Adviento et al 2014;Alfieri et al 2014).…”
Section: Relationship Between Genotype and Neurocognitive Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is high compared to the rate of approximately 5% in the general population [20]. Children with NF1 also display a significantly higher prevalence of autism spectrum disorder (ASD) symptomatology compared to the general population, with three recent studies reporting that between 11% and 29% of children with NF1 are rated within the severe range on the Social Responsiveness Scale [21] (a screening measure of ASD symptomatology); a range which is strongly associated with a clinical diagnosis of ASD [6,22,23]. Importantly, however, NF1 is associated with impairments in several domains that overlap with ASD (including delayed social, executive, and language skills), and so the true prevalence of ASD in NF1 may be lower than these reports would indicate [24].…”
Section: Psychological Comorbiditiesmentioning
confidence: 99%